The Small Key to the Treasure Chest: Endogenous Plant Peptides Involved in Symbiotic Interactions - Anna Mamaeva; Arina Makeeva; Daria Ganaeva (Plants)
Plant growth and development are inextricably connected with rhizosphere organisms. Plants have to balance between strong defenses against pathogens while modulating their immune responses to recruit beneficial organisms such as bacteria and fungi. In recent years, there has been increasing evidence that regulatory peptides are essential in establishing these symbiotic relationships, orchestrating processes that include nutrient acquisition, root architecture modification, and immune modulation. In this review, we provide a comprehensive summary of the peptide families that facilitate beneficial relationships between plants and rhizosphere organisms.